Effects of different percentages of body weight-supported treadmill training in Parkinson’s disease: a double-blind randomized controlled trial - Atan, Tuğba; Özyemişci Taşkıran, Özden; Bora Tokçaer, Ayşe; Kaymak Karataş, Gülçin; Karakuş Çalışkan, Aslı; Karaoğlan, Belgin (Turkish journal of medical sciences, 2019)
Body weight-supported treadmill training (BWSTT) might have greater effects than conventional treadmill training (TT) in neurological diseases such as Parkinson’s disease (PD). The aim of this study was to evaluate the effects of different percentages of BWSTT on gait, balance, quality of life, and fatigue in PD. Thirty-five patients with moderate to advanced PD were randomized into three BWSTT groups according to the supported percentage of body weight: 0% BWSTT (control group; unsupported TT), 10% BWSTT, or 20% BWSTT. Five patients were excluded due to early discharge and 30 patients completed BWSTT sessions lasting 30 min, 5 days a week, for 6 weeks during their inpatient rehabilitation stay. The primary outcome was 6-min walk distance (6MWD). Secondary outcomes were Unified Parkinson’s Disease Rating Scale (UPDRS), Berg Balance Scale (BBS), Nottingham Health Profile (NHP), Fatigue Impact Scale, and Fatigue Severity Scale scores. Measurements were performed before and after the training. The unsupported TT group demonstrated no significant improvement in the outcome measures after a 6-week training except for BBS and NHP emotional subscores. Moreover, the NHP pain subscore increased in the unsupported TT group after training. The 10% and 20% supported BWSTT groups demonstrated significant improvements in 6MWD (P = 0.004 and P < 0.001, respectively), UPDRS - motor score (P = 0.012 and P = 0.005, respectively), NHP pain subscore (P = 0.003 and P = 0.002, respectively), and fatigue (P = 0.005 for both) after training. The 20% BWSTT provided the highest improvement in balance among the three groups (P < 0.001) and greater relief of fatigue than 10% BWSTT (P = 0.002). Six weeks of BWSTT improved walking distance and balance ability, relieved fatigue, and additionally reduced pain in patients with moderate to advanced PD.